Estrogen blocks the protective action of melatonin in a behavioral model of ethanol-induced hangover in mice - Karadayian, A. G. (2012)
Melatonin has antioxidant and neuroprotective properties in human beings and experimental models, as well as 'anti-estrogenic' effects. Ethanol (EtOH) affects various behavioral parameters during a period known as ethanol-induced hangover. Our study evaluated the neuroprotective effect of melatonin on motor performance during ethanol hangover in male and female Swiss mice. The females were subjected to specific hormonal states: ovariectomized (OVX) and OVX estrogenized (OVX-E2). Mice received melatonin (25μg/ml) or vehicle in their drinking water for seven days and were given intraperitoneal (i.p.) injections of EtOH (3.8g/kg) or saline on the morning of the eighth day. Motor performance was evaluated by the tightrope test 6h after EtOH exposure (hangover onset). During ethanol hangover, males exhibited lower motor performance than controls (p<0.01) but pretreatment with melatonin significantly improved performance during hangover (p<0.05). In females, melatonin treatment before ethanol-induced hangover led to a better motor performance in OVX compared with intact females (p<0.01) and a lower performance in OVX-E2 compared with not-estrogenized OVX (p<0.05). Consequently, estrogen reversed the motor performance enhancement afforded by melatonin. We conclude that estrogen interferes with the protective action of melatonin on motor performance during ethanol hangover.